Kurdish EFL Teachers' Attitudes Towards the Use of Computer-Assisted Teacher Corrective Feedback in Teaching Writing Classes (Raparin Journal of Humanities (RJH), 2024)
Technology has recently played a crucial role in facilitating English language learning and teaching. A considerable body of literature has examined the influence of computer-assisted language learning (CALL) in ESL/EFL classrooms, specifically its mediating role in developing the learner’s language skills. This study aims to investigate the attitudes of Iraqi Kurdish EFL teachers towards using CALL tools to provide teacher-corrective feedback in EFL writing classrooms. It also seeks to determine whether the teachers’ demographic characteristics influence their attitudes and preferences towards using technology in their classes and computer-assisted teacher corrective feedback (CATCF). A quantitative research design was followed, and the data was collected from questionnaires administered to Kurdish EFL teachers at the public universities’ language centres in the Kurdistan Region of Iraq (KRI). The study's descriptive and inferential findings indicate that although Kurdish EFL instructors were sometimes anxious about using technology, they had an overall positive attitude towards CATCF, preferred using technology to teach their classes of writing, and were aware of the modern tools to teach writing classes. The results of this paper have some implications for EFL writing teachers.